2023
DOI: 10.3390/met13050850
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Laser Treatment Medium on the Surface Topography Characteristics of Laser Surface-Modified Resorbable Mg3Zn Alloy and Mg3Zn1HA Nanocomposite

Abstract: In this study, a Mg3Zn alloy and a Mg3Zn1HA nanocomposite were fabricated through disintegrated melt deposition, followed by the hot extrusion process. The specimens were subjected to fiber laser surface modification in air and demineralized water (DM) medium to determine the influence of the laser treatment medium on the microstructure, microhardness, grain size, and surface topography. During the laser treatment, the samples under the water medium produced a lower surface roughness when compared with the air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…Among magnesium-based materials, magnesium nanocomposites have emerged as highly promising materials. Numerous studies have demonstrated that incorporating nanoparticles into magnesium and its alloys can significantly enhance its thermal properties, static and dynamic responses, and machining and wear properties [2,8,[11][12][13][14][15][16][17][18]. The literature review indicates that no prior work has so far been conducted to explore the effects of cryogenic treatment on the response of magnesium nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…Among magnesium-based materials, magnesium nanocomposites have emerged as highly promising materials. Numerous studies have demonstrated that incorporating nanoparticles into magnesium and its alloys can significantly enhance its thermal properties, static and dynamic responses, and machining and wear properties [2,8,[11][12][13][14][15][16][17][18]. The literature review indicates that no prior work has so far been conducted to explore the effects of cryogenic treatment on the response of magnesium nanocomposites.…”
Section: Introductionmentioning
confidence: 99%